Jump Learning Approach: A Study on Improving Physical Literacy of Elementary School Children - Sri Wahyuni; Anggi Setia Lengkana; Encep Sudirjo (JUARA : Jurnal Olahraga, 2023)
Learning at school must be effective; sometimes, some obstacles make students want to avoid participating in sports learning because of internal and external deficiencies. The method used in this research is an experimental method with a one-group pretest-posttest design. The population in this study were 30 students of class VI at SDN Biru II using a systematic sampling technique. This study aimed to determine how much influence the play-jumping approach had on increasing the Physical Literacy of elementary school children. The method was to provide treatment for 12 meetings and use a questionnaire on motivation, self-confidence, physical competence, knowledge, and understanding of student learning. Data analysis techniques used the Normality Test and one sample t-test. All calculations were calculated using a software application. IBM SPSS stats 18. Based on the Determination test or R Square from the pre-test to the post-test results, it has a significant effect on the implementation of physical literacy activities that has a good influence on children's physical literacy. The results showed that the game-jumping learning approach positively increased students' physical literacy in physical education learning.